Predicting complete heart block after alcohol septal ablation for hypertrophic cardiomyopathy using a risk stratification model and clinical tool - Karimianpour, Ahmadreza; Heizer, Justin; Leaphart, Davis; Rier, Jeremy D.; Shaji, Shawn; Ramakrishnan, Viswanathan; Nielsen, Christopher D.; Fernandes, Valerian L.; Gold, Michael R. (Catheterization and cardiovascular interventions, 2021)
Background Alcohol septal ablation (ASA) is a proven method of septal reduction for patients with drug refractory, symptomatic hypertrophic obstructive cardiomyopathy (HOCM). This procedure is associated with a 6.5–11% risk of complete heart block (CHB). Objective The aim of this study is to determine factors that predict CHB and to develop a clinical tool for risk stratification of patients. Methods Patients were enrolled into an ongoing ASA study. A total of 636 patient procedures were included, 527 of whom were used in the development of the prediction tool, and 109 of whom were used for independent validation. Multivariate analysis was performed with odds ratios used to develop the clinical prediction tool. This was then internally and externally validated. Results Of the 527 in the prediction cohort, 46 developed CHB. The predictors of CHB were age ≥50 years, pre‐ASA left bundle branch block (LBBB), transient procedural high‐grade block, post‐ASA PR prolongation ≥68 ms, and new bifascicular block. An 11‐point clinical prediction tool was developed to classify these factors. Internal validation using a receiver operating characteristic curve revealed an area under the curve of 0.88 for the clinical prediction tool. External validation using 109 contemporary patients revealed a 98% negative predictive value, 24% positive predictive value, 75% sensitivity, and 81% specificity in high‐risk patients. Conclusion Among patients undergoing ASA, the risk of CHB can be predicted with easily obtained clinical and electrocardiographic factors. This clinical prediction tool allows identification of high‐risk patients who may benefit from additional monitoring and therapy.